2021
DOI: 10.3390/nu13103611
|View full text |Cite
|
Sign up to set email alerts
|

Skin Manifestations and Coeliac Disease in Paediatric Population

Abstract: Celiac disease (CD) is an immune-mediated enteropathy caused by gluten ingestion, affecting approximately 1% of the worldwide population. Extraintestinal symptoms may be present as the first signs of CD, years before the CD diagnosis is made. A great variety of extraintestinal manifestations may be associated with CD. Cutaneous manifestations represent the main extraintestinal manifestations, with dermatitis herpetiformis being the most common in patients with CD. In adults, it has been demonstrated that the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 137 publications
0
13
0
Order By: Relevance
“…The pathognomonic histology with immunohistochemistry or immunofluorescence shows granular IgA deposits and neutrophil infiltrates in the papillary dermis. Almost 85% of these patients with a Caucasian ethnicity carry HLA-DQ2 mutations while the remaining have HLA-DQ8[ 42 ]. Typically, only two-third patients with DH have villous abnormalities and one third of them have no enteropathy[ 43 ].…”
Section: Definite Indications For Screening For Cedmentioning
confidence: 99%
“…The pathognomonic histology with immunohistochemistry or immunofluorescence shows granular IgA deposits and neutrophil infiltrates in the papillary dermis. Almost 85% of these patients with a Caucasian ethnicity carry HLA-DQ2 mutations while the remaining have HLA-DQ8[ 42 ]. Typically, only two-third patients with DH have villous abnormalities and one third of them have no enteropathy[ 43 ].…”
Section: Definite Indications For Screening For Cedmentioning
confidence: 99%
“…CD is considered a childhood disease, however, up to 20% of adults diagnosed with CD are over 60 years of age [16]. CD manifests itself in a wide range of typical and atypical ways [17][18][19][20][21]. For more than three decades, the CD has been persistently underdiagnosed, and its clinical presentation has changed, leading to difficulties with CD diagnosis [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previous cohort studies showed a prevalence of DH to be 17–20% in untreated CD [ 23 , 24 , 25 ], however, in 2017, a 10-year cohort study in Finland showed a prevalence of only 4% [ 26 ]. Other dermatologic associations can include psoriasis [ 27 ], urticaria [ 28 ], leukocytoclastic vasculitis [ 29 ], alopecia areata, atopic dermatitis and hereditary angioneurotic oedema [ 30 ].…”
Section: Celiac Diseasementioning
confidence: 99%